Peran Religiusitas sebagai Variabel Moderasi dalam Hubungan Fear of Missing Out dan Influencer Marketing terhadap Perilaku Konsumtif Gen Z : Kabupaten Aceh Tengah - Ramdansyah Fitrah (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to evaluate the role of religiosity as a moderating variable in the relationship between fear of missing out (FoMO) and influencer marketing on the consumer behavior of Generation Z in Central Aceh Regency. The FoMO phenomenon, characterized by excessive anxiety when missing out on the latest information or trends, as well as the increasingly massive influence of influencer marketing through social media, is considered to have a significant contribution to the tendency of consumer behavior among Gen Z. Religiosity is considered a psychological factor that has the potential to control or weaken this consumer drive. This study uses the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The research objects are Gen Z born between 1997 and 2012, domiciled in Central Aceh Regency, actively following influencer accounts on social media, and have purchased products based on influencer recommendations. The determination of the number of samples refers to the general rules of SEM, which is a minimum of 100 respondents. The collected data were analyzed using SmartPLS software version 4.0. The results of the analysis show that FoMO and influencer marketing have a positive and significant effect on the consumer behavior of Gen Z in Central Aceh Regency. This means that the higher the level of FoMO and the more intense the exposure to influencer marketing strategies, the higher the respondents' consumer tendencies. Conversely, religiosity negatively influences consumer behavior, meaning that the higher the level of religiosity, the lower the consumer tendencies. Furthermore, religiosity has been shown to moderate the relationship between FoMO and influencer marketing on consumer behavior in a negative direction, thereby weakening the influence of both independent variables. These findings emphasize the important role of religiosity as a controlling factor in the digital era, which is rife with social pressure and marketing exposure through social media, especially among younger age groups who are vulnerable to consumer behavior.